Model Matematika Tipe SIQR Penyebaran Penyakit Difteri Dengan Pengaruh Vaksinasi - Putra, Kevin Pramana; Rosha, Media (Journal of Mathematics UNP, 2022)
The Bacteria Corynebacterium diphtheria is the cause of the possibly deadly infectious disease diphtheria. The esophagus and upper respiratory tract are attacked by these bacteria. This study’s objectives were to develop a mathematical model of diphtheria spreading of the SIQR tyoe with the influence of vaccination, analyze equilibrium point stability  and interpret  model simulation results. The type of research  is  theoretical research. This study uses descriptive methods to analyze theories about diphtheria. Two equilibrium points are obtained based on the analysis results of the SIQR model. When the basic reproduction number is less than 1, there exists an  asymptotically stable disease-free equilibrium point. On the other hand, if the basic reproduction number is greater than 1, there are two equilibrium points.Asymptotically stable endemic balance and  unstable disease-free balance. One way to control the spread of diphtheria is through vaccination. The higher the vaccination coverage, the more diseases will be eradicated from the population.